Archevolution: Recent Tools in Energy Conservation Design Process - Srisutapan, Awiroot (Journal of Architectural/Planning Research and Studies (JARS), 2002)
Through collective and analytical methods, this study mainly points out the types and properties of “Recent Tools” and how they operate in architectural design process. This paper also proposes suggestions and implementation methods considering the change of Thai contexts, especially in the areas of material selection, construction technology, energy conservation, renewable energy resources, environmental impact, occupants’ needs and quality of life. Moreover, the study provides further visions and integrated design guidelines to the architectural profession, including both educational and practical organizations. In addition, it is expected that future architecture would be evaluated by its “value” rather than “aesthetic” criteria.